Meningkatkan Prestasi Kerja Personil Polri - Swandewi, Ni Luh Gede; Benni Kusyana, Dewa Nyoman (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The importance of work performance is not only needed by profit-oriented organizations, but also by organizations that are oriented to public services and one of them is the Polresta Denpasar which throughout 2021 experienced low work performance of Satreskrim personnel which was marked by the low number of legal case settlements. This study aims to determine the effect of workload, work stress, and physical and non-physical work environment on the work performance of the Personnel of Satreskrim Polresta Denpasar. This research was conducted at the Denpasar Police Satreskrim with a population of 50 personnel and using the census method. Primary data collection was carried out by interview method at the pre-survey stage and continued with questionnaires to determine respondents’ perceptions of the variables studied. Then proceed with instrument testing using validity and reliability tests, followed by classical assumption tests and hypothesis testing using multiple linear regression analysis. The results partially prove that each of the independent variables, namely workload and work stress, has a negative and significant effect on work performance, and the work environment has a positive and significant effect on work performance.